Assessment and Management of Tomato Diseases under Plastic House Conditions in Lamjung - Neupane, S. K.; K.C., G. B.; Shrestha, S. M.; Neupane, A. C. (Journal of Agriculture and Environment, 2021)
An experiment was conducted under plastic houses at three farmers’ field, each farmer as a replication, in Tarku and Banhjakhet VDCs in Lamjung district during July to December 2010, to identify and manage major fungal diseases of tomato (variety Srijana) using chemicals and bio-pesticides. The treatments Bio-cure-F (Trichoderma viride, bio-fungicide), carbendazim (Bavistin, systemic fungicide) and Dithane M-45 (Mancozeb, contact fungicide) were applied as foliar spray. Control plot was maintained without application of any treatment. Mainly four fungal diseases, early blight (Alternaria solani), late blight (Phytophthora infestans), powdery mildew (Leveillula taurica) and septoria leaf spot (Septoria lycopersici) were recorded. Dithane M-45 appeared the best to control early blight, late blight and septoria leaf spot, followed by Bavistin and Bio-cure-F over control. Bavistin performed the best to control powdery mildew, followed by Dithane M-45 and Bio-cure F over control. Severity of fungal diseases appeared high on tomato in plastic house. Based on type of disease, Dithane M-45 or Bavistin is suggested to spray for the management.